The Effect of Picture and Text Prompts on Idea Formulation and Organization of Descriptive Text - Cut Mukramah; Faisal Mustafa; Diana Fauzia Sari (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
A prompt can be used as a medium to help students write a descriptive text. There is a lack of research on the type of prompts which can help students formulate and organize their ideas. Therefore, this study aims to determine whether there was a significant difference in the score of idea formulation and organization in a descriptive text between students writing with text prompts and those given a picture prompt. This research was quantitative research with a non-experimental design. The sample consisted of 45 second-grade junior high school students in a public school in Aceh, Indonesia. The data was collected by instructing students to write a descriptive text using a text prompt and another descriptive text using a picture prompt, which was later graded for idea formulation and organization using rubrics. The students’ scores between the two tests were compared using inferential statistics for hypothesis testing at the significance level of 0.05. The findings show that the students obtained significantly higher scores when a picture prompt was used than when they used a text prompt. Picture prompts helped students with an imaginative picture to be interpreted into a descriptive text. The findings help teachers identify which prompt is better when this type of text is a concern. Therefore, it is suggested that teachers use a picture prompt to facilitate students in formulating and organizing ideas in a descriptive text.